Answer:
X=-2
Y=-6
Step-by-step explanation:
Since both equations are already expressed in the simplest form of y, then we equate them to be equal hence
x-4=4x+2
Bringing like terms together
-4-2=4x-x
Solving both sides
-6=3x
Making x the subject then
X=-6/3=-2
Subsrituting the value of x into any of the initial equations
Y=x-4 then y=-2-4=-6
Therefore, the solution is
X=-2
Y=-6
Answer:
x = -1
Step-by-step explanation:
5 + 2x + 6 = x + 10
11 + 2x = x + 10
-x -x
11 + x = 10
-11 -11
x= -1
Statement 3: tri egc = tri egb
statement 4: tri ebc is equilateral.
reason 5: equilateral triangles have equal angles
Answer:
65.992
Step-by-step explanation:
LM/PL = RN/QR
LM / 113 = 73/ 125
LM =(73/125) * 113
Answer:
Ok
Step-by-step explanation: